2014
DOI: 10.1111/jth.12560
|View full text |Cite
|
Sign up to set email alerts
|

Differential associations of oral estradiol and conjugated equine estrogen with hemostatic biomarkers

Abstract: Background The risk of venous thrombosis (VT) associated with oral hormone therapy (HT) may differ by type of estrogen compound. Objective To compare the thrombotic profile of women using oral conjugated equine estrogens (CEE) with that of women using oral estradiol (E2). Methods In postmenopausal female health maintenance organization (HMO) members with no history of VT, we measured thrombin generation, levels of factor VII activity, antithrombin activity, and total protein S antigen. Mean levels of hemos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 43 publications
2
19
0
1
Order By: Relevance
“…We had limited power to analyze data by HT type, however most associations were similar by study. Studies suggest a lower risk of VT with estradiol or transdermal treatment than oral conjugated equine estrogens and we could not address this. To conserve power, we did not exclude women with pre‐baseline self‐reported VT, but we did adjust for this.…”
Section: Discussionmentioning
confidence: 97%
“…We had limited power to analyze data by HT type, however most associations were similar by study. Studies suggest a lower risk of VT with estradiol or transdermal treatment than oral conjugated equine estrogens and we could not address this. To conserve power, we did not exclude women with pre‐baseline self‐reported VT, but we did adjust for this.…”
Section: Discussionmentioning
confidence: 97%
“…Reanalysis of the WHI indicated an enhanced risk of stroke in association with oestrogen-only (HR 1.47 [95% CI 0.92–2.35]) and combined CEEs (HR 1.12 [95% CI 0.76–1.64]) when initiated >10 years after the onset of menopause. Our finding that CEEs, but not oestradiol, were associated with an increased stroke risk in some analyses may reflect thrombotic effects exerted by CEEs [ 36 , 37 ]. In all of the aforementioned studies addressing the timing of HT initiation, women could not be precisely allocated into early and late HT initiation groups; allocation was based on age rather than detailed information on timing [ 10 , 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies using animal models have demonstrated that treatment with oral CEE improves arterial function (Ceravolo et al, 2013) and, therefore, may be beneficial to the cardiovascular system. However, transdermal estrogen (Speroff, 2010) and oral CEE (Peeyananjarassri and Baber, 2005) have also been associated with increased risk of venous thrombosis (Hu and Grodstein, 2002;Blondon et al, 2014;Smith et al, 2014), suggesting that CEE may display opposing effects in arteries and veins.…”
Section: Introductionmentioning
confidence: 99%